O ensino religioso e a proposta de reorientação curricular do Estado de Goiás em 2009 - Cunha, Luzeni Martins da (2019)
This dissertation understood the religious teaching in public schools of the State of Goiás, in view of the relationship of two central points: first the curricular proposal of 2009 and then the practices performed in high school (CEPI) Teaching Center in Period General-purpose integral Dr. Sebastião Gonçalves on city of Uruaçu. We can thus understand the religious teaching and their moral conceptions and practices. From these assumptions, we carried out an investigation into this new proposal of this teaching, with the problem of research which the sense of the proposal of the Government of the State of Goiás from 2009 for religious teaching in public schools to the State training of students, as these young people receive religious education in their families? About the background of this work, is the need for a reflection on the historical aspects of the religious teaching, performing a reading of historical, political and thematic texts on religious education, such as Azevedo (2004); Junqueira (2008, 2017) and Brandenburg. For the development of this work, we use a search of observational documentary and, in this sense, the bibliography to give theoretical support and later a documentary part so we can relate a type of information with other to understand how are conflicting or not. So, we understand the reorientation to the religious education of 2009, religious education practices and especially the applicability of this in high school so we can understand the Polyvalent acceptance or not on the part of teachers, students and the community school, which is also an integral part of life at school. Therefore, understood as the religious education manifests itself in the education system in Goiás, from the action of Jesuit priests in the context of colonial Brazil and, later, in Goiás; at the end of the survey, we understand the proposal on CEPI-State College.